Characterization of Transferrable Mechanisms of Quinolone Resistance (TMQR) among Quinolone-resistant Escherichia coli and Klebsiella pneumoniae causing Urinary Tract Infection in Nepalese Children - Raj Kumar Shrestha; Ashmita Thapa; Dhruba Shrestha; Sabi Pokhrel; Anubhav Aryal; Rupika Adhikari; Nipun Shrestha; Bhim Gopal Dhoubhadel; Christopher M Parry (BMC, 2023)
Abstract Background Transferrable mechanisms of quinolone resistance (TMQR) can lead to fluoroquinolone non-susceptibility in addition to chromosomal mechanisms. Some evidence suggests that fluoroquinolone resistance is increasing among the pediatric population. We sought to determine the occurrence of TMQR genes among quinolone-resistant E. coli and K. pneumoniae causing urinary tract infections among Nepalese outpatient children (< 18 years) and identify molecular characteristics of TMQR-harboring isolates. Methods We performed antimicrobial susceptibility testing, phenotypic extended-spectrum β-lactamase (ESBL) and modified carbapenem inactivation method tests, and investigated the presence of six TMQR genes (qnrA, qnrB, qnrS, aac(6')-Ib-cr, oqxAB, qepA), three ESBL genes (bla CTX−M, bla TEM, bla SHV), and five carbapenemase genes (bla NDM, bla OXA−48, bla KPC, bla IMP, bla VIM). The quinolone resistance-determining region (QRDR) of gyrA and parC were sequenced for 35 TMQR-positive isolates. Results A total of 74/147 (50.3%) isolates were TMQR positive by multiplex PCR [aac(6')-Ib-cr in 48 (32.7%), qnrB in 23 (15.7%), qnrS in 18 (12.3%), qnrA in 1 (0.7%), and oqxAB in 1 (0.7%) isolate]. The median ciprofloxacin minimum inhibitory concentration of TMQR-positive isolates (64 µg/mL) was two-fold higher than those without TMQR (32 µg/mL) (p = 0.004). Ser-83→Leu and Asp-87→Asn in GyrA and Ser-80→Ile in ParC were the most common QRDR mutations (23 of 35). In addition, there was a statistically significant association between TMQR and two β-lactamase genes; bla CTX−M (p = 0.037) and bla TEM (p = 0.000). Conclusion This study suggests a high prevalence of TMQR among the quinolone-resistant E. coli and K. pneumoniae isolates causing urinary tract infection in children in this area of Nepal and an association with the carriage of ESBL gene. This is a challenge for the management of urinary infections in children. Comprehensive prospective surveillance of antimicrobial resistance in these common pathogens will be necessary to devise strategies to mitigate the emergence of further resistance.